Potential of Farm Forestry in Carbon Sequestration - Singh, T. P. (Indian Forester, 2003)
The Kyoto Protocol allows assistance being given for sustainable development as a contribution to carry out the ultimate objective, ie. Reduction of GHG emissions. Forests act as carbon sinks, therefore, farm forestry can be immensely useful for CO2 sequestration. The article presents a case study in this context from Pilibhit District (Uttar Pradesh). The land holders, divided into three categories - small, medium and large holdings, the majority ofland being with medium landholders. Medium farmers grow more trees on their lands as compared to other categories. Usually, Eucalypts, Poplar, Teak, Kadam are being planted. It is estimated that total biomass production is likely to be 32,800 tonnes/year and the stored carbon 16,400 tonnes/year. Thus farm forestry holds tremendous potential for sequestering and storing carbon.